2019
DOI: 10.1038/s41598-019-51094-z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental challenge with bovine respiratory syncytial virus in dairy calves: bronchial lymph node transcriptome response

Abstract: Bovine Respiratory Disease (BRD) is the leading cause of mortality in calves. The objective of this study was to examine the response of the host’s bronchial lymph node transcriptome to Bovine Respiratory Syncytial Virus (BRSV) in a controlled viral challenge. Holstein-Friesian calves were either inoculated with virus (103.5 TCID50/ml × 15 ml) (n = 12) or mock challenged with phosphate buffered saline (n = 6). Clinical signs were scored daily and blood was collected for haematology counts, until euthanasia at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 52 publications
2
68
0
Order By: Relevance
“…Ninety-three percent (26,518) of the ROCs within 2 kb upstream of a gene were closest to a gene expressed in the BLN (Additional file 3 ). Of the protein-coding genes expressed in the BLN [ 22 ], 82% (11, 047) had a ROC either within the gene or within 2 kb upstream of the gene. Twenty-two percent (1450) of the protein coding genes not expressed in the BLN had a ROC either within the gene or within 2 kb upstream of the gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ninety-three percent (26,518) of the ROCs within 2 kb upstream of a gene were closest to a gene expressed in the BLN (Additional file 3 ). Of the protein-coding genes expressed in the BLN [ 22 ], 82% (11, 047) had a ROC either within the gene or within 2 kb upstream of the gene. Twenty-two percent (1450) of the protein coding genes not expressed in the BLN had a ROC either within the gene or within 2 kb upstream of the gene.…”
Section: Resultsmentioning
confidence: 99%
“…An understanding of the identity of the variation within the bovine genome which confers variation in resistance to BRD is needed to incorporate genetic variants into breeding programmes designed to breed robust animals with increased resistance to BRD infection. In a previous study, we identified differentially expressed genes [ 22 ] and miRNAs (unpublished observations) in the bronchial lymph nodes (BLN) (the site of antigen presentation and activation of immune effector cells), of Holstein-Friesian calves experimentally challenged with BRSV. Additionally, the transcriptional response to infection with several pathogens involved in the bovine respiratory disease complex (BRDC) in BLN [ 23 ], lung and multiple lymphoid tissues [ 24 ] has previously been described in US Angus x Hereford crossbred beef steers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respiratory epithelial cells are the first line of defence and function as a physical barrier to protect against invading pathogens (Agnes et al, 2013;Eberle et al, 2016;Cozens et al, 2019), including BRDC-causing pathogens (Liu et al, 2018;Johnston et al, 2019). Under normal conditions, the upper respiratory tract epithelial cells are responsible for inhibiting microbial invasion by trapping pathogens to adherence factors on the cellular surface (Masaki et al, 2011;Mata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…BRSV infections in cattle augment the number of adherent bacteria (Tjønehøj et al, 2003;Tizioto et al, 2015) by destroying the normal transport mechanism used by airway epithelial cells, allowing the flow of bacteria through the lower airway and lung (Spilki et al, 2006;Jordan et al, 2015). Furthermore, BRSV infection of the lower respiratory tract can stimulate a substantial increase in bacterial load and lead to secondary complications and the development of severe pneumonia (Johnston et al, 2019).…”
Section: Introductionmentioning
confidence: 99%